2019
DOI: 10.1111/ejh.13323
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of IGF‐1 receptor is useful in the differential diagnosis of essential thrombocytosis from reactive thrombocytosis

Abstract: The 2016 revision to the World Health Organization (WHO) classification of myeloid neoplasms and acute leukemia lists the criteria for diagnosing essential thrombocythemia (ET) as (a) platelet count more than 450 × 10 9 /L; (b) bone marrow biopsy showing proliferation mainly of the megakaryocyte lineage with increased numbers of enlarged, mature megakaryocytes with hyperlobulated nuclei; no significant increase or left shift in neutrophil granulopoiesis or erythropoiesis; and very rarely a minor (grade 1) incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Wang et al attempted to use amount of IGF-1 receptor in the differential diagnosis. The levels of IGF-1R were significantly elevated in ET groups compared to in RT groups or controls ( 18 ). Ryningen et al reported that RT or thrombocytopenia will increase platelet turnover, thus increasing the circulating number of reticulated platelets in myeloproliferative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al attempted to use amount of IGF-1 receptor in the differential diagnosis. The levels of IGF-1R were significantly elevated in ET groups compared to in RT groups or controls ( 18 ). Ryningen et al reported that RT or thrombocytopenia will increase platelet turnover, thus increasing the circulating number of reticulated platelets in myeloproliferative disorders.…”
Section: Discussionmentioning
confidence: 99%